A Questıonnaıre Survey-Hepatıt B And Cross Infectıon Control In Orthodontıcs - Müyesser Saraç; Aylin Sezen Yalçın (Galenos Yayinevi, 1995)
A questionnaire survey was carried out to test orthodontists with respect to hepatit B and to obtain information about glove use and sterilization procedures they used. Results indicated that 8 persons have had disease and 32,3 percent of the other 102 ortodontists were vaccinated against Hepatit B 48 percent of the orthodontists never used protective barriers. Heat sterilization methods and chemical solutions were used commonly Vaccination, using protective barriers, effective sterilization procedures must be taken in to consideration carefully by orthodontists against hepatit B virus transmitted by blood and saliva. Protection of the orthodontic patients as young adults and children is important because the transmission and persistance of the virus more common in the these age groups.